PERAN HEPARIN DALAM ANGIOGENESIS, EPITELIALISASI DAN PENYEMBUHAN LUKA BAKAR - Asparini, Ruby Riana (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2011)
Heparin was initially used in small doses as an anticoagulant in the treatment of burns. It turned out that in addition to the anticoagulant, heparin in larger doses can be used as an anti-inflammatory, accelerate angiogenesis (Polykratis, et al., 2004), cell growth and development (Sasisekharan and Venkataraman, 2000) so as to accelerate wound healing (Saliba, 2001; Galvan , 1996). In some countries heparin has been used as a standard therapy treatment of burns (Saliba, 2001). Heparin is one of highest endogenous glycosaminoglycans (GAGs) besides heparan sulfate (HS), keratin sulfate, dermatan sulfate, chondroitin 4-sulfate, chondroitinHS-6-sulfate and hyaluronic acid. heparin are the most acid and are highly sulfated, is the most GAGs widely used in burns as anti-inflammatory, to reduce edema, enhance angiogenesis and accelerate epitelialization (Saliba, 2001). Several studies have revealed the role of heparin in the treatment of burns. Keywords : Heparin, angiogenesis, epitelialization, treatment of burns